OPTIMASI BIAYA DISTRIBUSI BERAS MISKIN (RASKIN) MENGGUNAKAN MASALAH TRANSPORTASI TAK SEIMBANG - Ilwaru, Venn Yan Ishak; Lesnussa, Yopi Andry; Tentua, Jesica (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Rice is the staple food for the majority of Indonesian population. As the population increases, the need for rice also increases. Rice distribution is very important in terms of budget and time efficiency. The purpose of this research was to minimize the distribution costs of poor rice (RASKIN) by using the ASM (Abdul, Shaleh, Maliki) modification method, so that the distribution costs obtained were optimal. This research was conducted at Perum BULOG Ambon Sub Divre Maluku. Based on the research results, it shows that by using the ASM modification method the distribution costs incurred by Perum BULOG Ambon Sub Divre Maluku is Rp. 1,091,121,022.